Influence of Solvent Representation on Nuclear Shielding Calculations of Protonation States of Small Biological Molecules - Roggatz, Christina C; Lorch, Mark; Benoit, David M (Journal of chemical theory and computation, 2018)
In this study, we assess the influence of solvation on the accuracy and reliability of isotropic nuclear magnetic shielding calculations for amino acids in comparison to experimental data. We focus particularly on the performance of solvation methods for different protonation states, as biological molecules occur almost exclusively in aqueous solution and are subject to protonation with pH. We identify significant shortcomings of current implicit solvent models and present a hybrid solvation approach that improves agreement with experimental data by taking into account the presence of direct interactions between amino acid protonation state and water molecules.